2005
DOI: 10.1021/jf0500031
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Antiadhesive Fraction(s) in Nonimmunized Egg Yolk Powder:  In Vitro Study

Abstract: The presence of antiadhesive component(s) in the hen egg yolk against foodborne pathogens was anticipated from results of a previous animal study conducted by the authors. The previous work showed egg yolk powder without specific antibodies is effective in controlling Salmonella enteritidis,Salmonella typhimurium, and Escherichia coli O157:H7 colonization in laying hens. Therefore, this study was necessary to locate the activity and identify the effective component(s). In vitro experiments were conducted using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 41 publications
(50 reference statements)
0
12
0
1
Order By: Relevance
“…Inhibition of type III secretion by cells treated with nonimmune egg powder may have contributed to the ability of the control egg powder preparation to reduce the adherence of E. coli O157:H7 to HeLa cells. The inhibition of EHEC adherence by control egg powder was not entirely unexpected, as a previous investigation revealed that the high‐density lipoprotein (HDL) component of the granular fraction of chicken egg yolks has a distinct inhibitory effect on the adhesive potential of E. coli O157:H7 (Kassaify et al. 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Inhibition of type III secretion by cells treated with nonimmune egg powder may have contributed to the ability of the control egg powder preparation to reduce the adherence of E. coli O157:H7 to HeLa cells. The inhibition of EHEC adherence by control egg powder was not entirely unexpected, as a previous investigation revealed that the high‐density lipoprotein (HDL) component of the granular fraction of chicken egg yolks has a distinct inhibitory effect on the adhesive potential of E. coli O157:H7 (Kassaify et al. 2005).…”
Section: Discussionmentioning
confidence: 93%
“…This may be explained by the presence of components such as high‐density lipoproteins (Kassaify and others ) or sialyloligosaccharides and their derivatives (Sugita‐Konishi and others ).…”
Section: Preharvest Methods For Reducing the Risk Of Salmonella Contamentioning
confidence: 99%
“…The authors hypothesized that egg yolk products might have antimicrobial components. It was later found that the fractions conveyed an antiadhesive effect against the food-borne pathogens instead of a direct antimicrobial activity (Kassaify et al 2005). Thus, the fractions itself could either (i) adhere directly to the surface of pathogens, therefore, blocking specific sites required for microbial adherence, or (ii) act indirectly to prevent pathogens' entry by inducing the activation of immune system components responsible of denying access to pathogens into the chicken body from the epithelial surface.…”
mentioning
confidence: 99%